(untitled) (Asian Journal of Medical and Biological Research, 2019)
Despite efforts to eliminate female genital mutilation and cutting, the harmful practice has persisted in southwest Nigeria. There is an urgent need for accurate data highlighting predictors of the practice so that interventions to eliminate it can be effective. A population-based, cross-sectional survey of women in Ado – Ekiti Local Government Area was conducted to address this need. FGM/C prevalence was 67.2%, and 94% of the women interviewed were aware of the practice. Although most, 142 (39.3%), of the women heard of FGM/C from healthcare personnel, half, 181 (50.1%), of the respondents noted that healthcare providers performed the FGM/C in the community. Young and middle-aged women, of Yoruba extraction who were married, and multiparous, were significantly more likely to have undergone FGM/C. Also, the likelihood of having experienced FGM/C was more among women who were presently employed (irrespective of the class of occupation), had female children, and with a poor perception about FGM/C. After including characteristics with p < 0.05 into multivariate logistic regression model with practice of FGM/C as the dependent variable, perception about FGM/C (AOR: 0.42; 95% C.I.: 0.24 – 0.72; p = 0.002), employment as a skilled worker (AOR: 0.30; 95% C.I.: 0.13 – 0.69; p = 0.005) and being of Yoruba (AOR: 0.07; 95% C.I.: 0.02 – 0.25; p < 0.0001) and Igbo extraction (AOR: 0.15; 95% C.I.: 0.02 – 0.93; p = 0.042), were independently associated with the experience of FGM/C in the study population. Scaling up media involvement and inclusion of FGM/C facts in school texts and curricula, legal sanctions for erring healthcare workers, female re-orientation to correct wrong perception about FGM/C’s supposed benefits, and accurate data for targeted public health interventions are recommended. Asian J. Med. Biol. Res. June 2019, 5(2): 146-152